Lipoprotein lipase regulates hematopoietic stem progenitor cell maintenance through DHA supply - Chao Liu (Nature Portfolio, 2018)
Lipoprotein lipase (LPL) hydrolyzes triglycerides to supply free fatty acids (FFAs) to muscle for energy and adipocytes for storage. Here, the authors demonstrate that Lpl and its product, the FFA docosahexaenoic acid (DHA) are required for haematopoietic stem progenitor cell expansion during zebrafish embryogenesis.